Early Tracheostomy in Prolonged Mechanical Ventilation Due to Severe Head Injury to Prevent Ventilator-Associated Pneumonia (VAP) - Ananda, Pratama; Sony (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: Early tracheostomy needs to be considered if a ventilator is expected to be used for an extended period of time. Early tracheostomy is recommended since it improves respiratory function, reduces the risk of ventilator-associated pneumonia (VAP), improves patients' comfort level, cleanses secretions in the throat, reduces laryngeal ulceration, improves mobilization, and speech efforts, and allows treatment outside the intensive care unit (ICU). Case Series: Four cases of severe head injury with an early tracheostomy, which illustrate the prevention of VAP, were reported. In these four cases, early tracheostomy was performed (£ 4 days) considering the initial critical GCS, the location of the lesion, and that mechanical ventilation was expected to be used for an extended period of time. During treatment, no VAP signs were detected, evidenced by Clinical Pulmonary Infection Score (CPIS), Rontgen thorax, and sputum culture examinations. Based on a meta-analysis study, early tracheostomy reduces mortality due to VAP by up to 50% and reduces the length of stay in ICU compared to delayed/late tracheostomy (> 10 days) or prolonged intubation (> 14 days). Conclusion: In the study cases, early tracheostomy (<4 days) was found to be associated with reduced ventilation time and shortened ICU and hospital stays without an increased risk of VAP. VAP prevention efforts are carried out by applying early tracheostomy and VAP bundle as well. Early tracheostomy offers more benefits than prolonged intubation or delayed/late tracheostomy.